1998
DOI: 10.1359/jbmr.1998.13.10.1633
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polymorphism in the Promoter Region for the Human Osteocalcin Gene: The Possibility of a Correlation with Bone Mineral Density in Postmenopausal Japanese Women

Abstract: We present a polymorphism of the human osteocalcin gene (also known as BGP, for bone Gla protein) due to a 1 base pair (bp) substitution from cytosine to thymine at position 298 nucleotides (nt), which is at position 198 nt upstream from the BGP exon 1. This mutation was detected by single-strand conformation polymorphism analysis after polymerase chain reaction for the osteocalcin gene fragment (326 bp) and sequencing analysis. The cytosine/thymine polymorphism can be defined by restriction fragment length po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…(38,39) The studies that looked at BMD have yielded variable results. (21)(22)(23)(24)(25)(26)34,39) In this study, we examined the relationships between genetic variation in and around the osteocalcin gene and circulating OC, BMD, and body fat and the implication for prediction of fracture occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(38,39) The studies that looked at BMD have yielded variable results. (21)(22)(23)(24)(25)(26)34,39) In this study, we examined the relationships between genetic variation in and around the osteocalcin gene and circulating OC, BMD, and body fat and the implication for prediction of fracture occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the absence of tagging singlenucleotide polymorphism (SNP) data at that time, SNPs were selected based on relative position in relation to the gene, minor allele frequency in the white population, and distance between the polymorphisms. In addition to the most commonly reported SNP, rs1800247 (also known as HindIII) at nucleotide 298 in the promoter region of the osteocalcin gene, (10,21,22,25,(32)(33)(34) three additional SNPs were chosen. These SNPs were rs1543294 (C/T) located 3 0 of the osteocalcin gene and close to the PMF1 (polyamine-modulated factor 1) gene; rs2842880 (C/T) located in intron 13, and rs933489 (G/A) located in intron 14 of the EST1B (EST1B-like protein, S-mg5 homologue) gene.…”
Section: Osteocalcin Sequencing and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed associations of the osteocalcin gene with BMD in various ethnic populations [23,24,25,26,27,28,29]. Results regarding the association between serum osteocalcin and osteocalcin gene polymorphisms with BMD and bone metabolism markers vary; thus, the main objectives of this study were as follows: (1) to evaluate the association of serum osteocalcin with BMD and markers of bone metabolism in postmenopausal Chinese women and (2) to observe the relationships of single-nucleotide polymorphisms (SNPs) in and around the osteocalcin gene with serum osteocalcin, BMD, and markers of bone metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalarda BGLAP geni promotor bölgesi -298 C/T poliorfizmi osteoporozla ilişkilendirilmiştir (28). Bu kısım maksimum promotor aktivitesine sahiptir, -298T allelinin OS geninin promoter aktivitesini azalttığı bildirilmiştir BGLAP geninin düşük ekspresyonu, kemik organik matriks bileşiminde osteokalsin düzeyini azaltmaktadır (29,30). Kollajen Tip1 allfa 1 (Col1A1) ve (Col1A12) Genleri: Kollajen, memelilerde büyük oranda fibroblast ve osteoblastlar tarafından üretilir.…”
Section: Polimorfizm çAlışmalarıunclassified